Imperfect transmission conditions for a thin weakly compressible interface. 2D problems (Archives of Mechanics - Test, 2004)
Imperfect transmission conditions are evaluated in the case of weakly compressible elastic interphase between different bonded elastic materials. It is shown that the corresponding conditions can be different in comparison with those for the elastic compressible interface.